2014
DOI: 10.1099/jmm.0.067108-0
|View full text |Cite
|
Sign up to set email alerts
|

The value of signs and symptoms in differentiating between bacterial, viral and mixed aetiology in patients with community-acquired pneumonia

Abstract: Current diagnostics for community-acquired pneumonia (CAP) include testing for a wide range of pathogens, which is costly and not always informative. We compared clinical and laboratory parameters of patients with CAP caused by different groups of pathogens to evaluate the potential for targeted diagnostics and directed treatment. In a prospective study, conducted between April 2008 and April 2009, adult patients with CAP were tested for the presence of a broad range of possible respiratory pathogens using bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 53 publications
9
62
2
7
Order By: Relevance
“…The most commonly identified viruses were influenza in 18 studies [3, 6, 7, 10, 11, 17-19, 21, 23, 26, 27, 29, 31, 32, 34-36], rhinovirus in eight studies [1,5,8,12,22,24,25,28], respiratory syncytial virus in three studies [2,9,33] and coronavirus in two studies [20,30]. Meta-analyses revealed that the proportion of infection by influenza (31 studies) was 8% (95% CI 6.3-9.6%; I 2 =91.9%), by rhinovirus (25 studies) was 5.7% (95% CI 4.3-7.1%; I 2 =90.3%), by respiratory syncytial virus (29 studies) was 2.2% (95% CI 1.6-2.8%; I 2 =80%) and by coronavirus (18 studies) was 3.3% (95% CI 2.3-4.2%; I 2 =80.2%).…”
Section: Individual Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly identified viruses were influenza in 18 studies [3, 6, 7, 10, 11, 17-19, 21, 23, 26, 27, 29, 31, 32, 34-36], rhinovirus in eight studies [1,5,8,12,22,24,25,28], respiratory syncytial virus in three studies [2,9,33] and coronavirus in two studies [20,30]. Meta-analyses revealed that the proportion of infection by influenza (31 studies) was 8% (95% CI 6.3-9.6%; I 2 =91.9%), by rhinovirus (25 studies) was 5.7% (95% CI 4.3-7.1%; I 2 =90.3%), by respiratory syncytial virus (29 studies) was 2.2% (95% CI 1.6-2.8%; I 2 =80%) and by coronavirus (18 studies) was 3.3% (95% CI 2.3-4.2%; I 2 =80.2%).…”
Section: Individual Virusesmentioning
confidence: 99%
“…For the outcome short-term mortality, we pooled data from 13 studies [2,3,6,7,24,26,28,29,[31][32][33][34][35]. The odds of death were higher in patients with viral infection, but there was no statistical significance (OR 1.3, 95% CI 0.8-2.16; p=0.283; I 2 =44.1%) (figure 3).…”
Section: Short-term Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…La diferenciación entre pacientes con cuadro clínico típico o atípico (según la presencia o ausencia, respectivamente, de 3 o más de las siguientes manifestaciones: inicio brusco, escalofríos, dolor pleurítico, expectoración purulenta, semiología franca y leucocitosis) no tiene utilidad predictiva absoluta, pero se correlaciona con una mayor o menor probabilidad de agentes bacterianos convencionales o atípicos, y sigue siendo de utilidad práctica, particularmente para pacientes con NAC poco grave 22,23 .…”
Section: Diagnóstico Clínicounclassified
“…The same is true when faced with a patient with fever with no respiratory manifestations. 22,23 Apart from these general clinical variables, various pathogens have been correlated with specific clinical and epidemiological findings (Table 1). The presence of pleuritic pain or very obvious symptomatology can be of considerable use.…”
Section: Clinical Diagnosismentioning
confidence: 99%